Scalable Synthesis of Pure and Stable Hexaaminobenzene Trihydrochloride - Mahmood, Javeed; Kim, Dongwook; Jeon, In-Yup; Lah, Myoung Soo; Baek, Jong-Beom (Synlett, 2013)
Synthesis of hexaaminobenzene (HAB) in pure and stable form has remained as an important challenge for a long time, since it is a fascinating synthon for the synthesis of aromatic nitrogenous compounds having many interesting applications. Here, we report an improved synthesis of pure and stable HAB form using modified catalytic hydrogenation in aqueous acidic medium. The structure of needle-shaped HAB crystals was confirmed by single-crystal X-ray diffraction study. The synthetic protocol could thus be a simple, but efficient for the large-scale synthesis of highly pure and stable HAB.
Keywords: hexaaminobenzene; palladium; reduction; TATB; TNA